Role of circulating free DNA in evaluating clinical tumor burden and predicting survival in Chinese metastatic colorectal cancer patients - Xiaojing Xu; Yiyi Yu; Minna Shen; Mengling Liu; Shengchao Wu; Li Liang; Fei Huang; Chenlu Zhang; Wei Guo; Tianshu Liu (BMC Cancer, 2020)
Abstract Background The aim of this study was to explore the utility of circulating free DNA (cfDNA) in the evaluation of clinical tumor burden and survival in Chinese patients with metastatic colorectal cancer (mCRC) and to preliminarily summarize some metastatic characteristics associated with mutational status. Methods A panel covering a total of 197 hotspot mutations of KRAS, NRAS, BRAF and PIK3CA was used to evaluate the mutational status in plasma by next-generation sequencing (NGS) technology in 126 patients with mCRC. An amplification-refractory mutation system (ARMS) was used to analyze genomic DNA from matched tissue samples. Clinical markers including carcinoembryonic antigen (CEA), carbohydrate antigen 199 (CA199), carbohydrate antigen 125 (CA125), neuron-specific enolase (NSE) and lactate dehydrogenase (LDH) in serum and the sum of all tumor diameters on CT or PET/CT were collected to indicate clinical tumor burden. The correlations between cfDNA and clinical tumor burden were analyzed using Pearson correlation and linear regression models. The median progression-free survival (PFS) and 1-year overall survival (OS) rates were calculated by Kaplan-Meier (K-M) survival analysis. Results Of the 126 enrolled patients, patients who were tested positive for mutations in plasma accounted for 45.2% (57/126). Mutations in KRAS, NRAS, BRAF and PIK3CA were detected in 37.3% (47/126), 1.6% (2/126), 3.2% (4/126) and 13.5% (17/126) of patients, respectively. The overall concordance rate of mutational status between plasma and matched tissues was 78.6% (99/126). Sixteen patients had mutations in plasma that were not detected in tissue, including some rare hotspot mutations. The cfDNA concentration was significantly correlated with the levels of clinical markers, especially CEA (P < 0.0001, Pearson r = 0.81), LDH (P < 0.0001, Pearson r = 0.84) and the sum of tumor diameters (P < 0.0001, Pearson r = 0.80). Patients with a high cfDNA concentration (> 17.91 ng/ml) had shorter median progression-free survival (6.6 versus 11.7 months, P < 0.0001) and lower 1-year overall survival rate (56% versus 94%, P < 0.0001) than those with a low cfDNA concentration (≤17.91 ng/ml). The most common metastatic site was the liver (77.8%), followed by the lymph nodes (62.7%), lung (40.5%), peritoneum (14.3%) and bone (10.3%), in all patients. There was no significant difference in metastasis between different mutational statuses. Conclusion Analyzing mutations in plasma could provide a more comprehensive overview of the mutational landscape than analyzing mutations in tissue. The cfDNA concentration could be a quantitative biomarker of tumor burden and could predict survival in Chinese patients with mCRC.